2016
DOI: 10.1007/978-3-658-14626-9
|View full text |Cite
|
Sign up to set email alerts
|

Bürgerenergie in Deutschland

Abstract: Weltweite Verteilungskämpfe um knappe Energieressourcen und der Klimawandel mit seinen Auswirkungen führen zu globalen, nationalen, regionalen und auch lokalen Herausforderungen, die Gegenstand dieser Publikationsreihe sind. Die Beiträge der Reihe sollen Chancen und Hemmnisse einer präventiv orientierten Energie-und Klimapolitik vor dem Hintergrund komplexer energiepolitischer und wirtschaftlicher Interessenlagen und Machtverhältnisse ausloten. Themenschwerpunkte sind die Analyse der europäischen und internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 263 publications
0
3
0
2
Order By: Relevance
“…Related to the previous point, we would like to highlight the question of gender equality. Previous research has shown that non-male people are underrepresented in local energy projects in general (Tsagkari 2022) and CE projects in particular (Radtke 2016). The early beginnings of CE development on AErø were no exception to this as the original group that started wind and solar projects consisted exclusively of men.…”
Section: Democratisation and Participationmentioning
confidence: 99%
“…Related to the previous point, we would like to highlight the question of gender equality. Previous research has shown that non-male people are underrepresented in local energy projects in general (Tsagkari 2022) and CE projects in particular (Radtke 2016). The early beginnings of CE development on AErø were no exception to this as the original group that started wind and solar projects consisted exclusively of men.…”
Section: Democratisation and Participationmentioning
confidence: 99%
“…For individual participation in community energy access to information and knowledge about existing participation opportunities are in turn major drivers of participation [82]. But also additional prerequisites such as financial requirements (acquisition of shares) and the minimum duration of participation determine participation (sometimes indirectly) [82]. While all these factors play a role motives to join energy communities remain diverse [77].…”
Section: Local Conditions For Collective Empowerment In Recsmentioning
confidence: 99%
“…While all these factors play a role motives to join energy communities remain diverse [77]. In Germany for instance motives to join an energy community are in tendency less revenue driven and tend to be more ideational (e.g., contributing to the energy transition) for low-income groups and academics than compared to high income groups [82]. With respect to equality of chances, and equity Park (2012) acknowledges differences between communities and their capacity to get involved in renewable energies [70].…”
Section: Local Conditions For Collective Empowerment In Recsmentioning
confidence: 99%
“…Jedoch nur knapp 14% des Jahresumsatzes an pflanzlichen Arzneimitteln in Deutschland im Jahr 2020 (ca. 1,4 Milliarden €) basierten auf einer ärztlichen Verordnung 4 . Dies verdeutlicht, wie wichtig es ist, die vorhandene Evidenz zu Phytotherapie systematisch aufzuarbeiten und adäquate Empfehlungen in medizinische Leitlinien zu integrieren.…”
Section: Introductionunclassified